Sharia Meets Digital Finance: How Innovativeness Constructs Influence Islamic Fintech Adoption - Johari, Mohamad; Supiandi, Supiandi; Loreño, Dustin Tarinque (STI Policy and Management Journal, 2025)
This study investigates the key determinants of Islamic FinTech adoption by extending the Technology Acceptance Model (TAM) framework to include Perceived Sharia Compliance and Perceived Innovativeness as antecedent variables. A quantitative approach was employed using survey data from 380 Islamic bank customers in Indonesia who had experience with Islamic FinTech services. The findings reveal that both antecedent variables positively influence Perceived Ease of Use and Perceived Usefulness, confirming the relevance of both religious values and innovation perceptions in shaping users’ attitudes. Consistent with TAM, Perceived Ease of Use impacts Perceived Usefulness and Behavioral Intention, while Perceived Usefulness is a key driver of customers’ intention to utilize Islamic FinTech services. Additionally, Behavioral Intention significantly predicts Actual Adoption, which subsequently enhances Customers’ Satisfaction. Mediation analysis results further shows that Behavioral Intention partially mediates the relationships between TAM beliefs and Actual Adoption. This study has contributed to the growing body of Islamic banking literature by enriching the TAM framework with culturally relevant and innovation-oriented constructs. The findings provide important insights for Islamic banks and FinTech service providers, highlighting the needs to develop Shariacompliant, user-friendly, and technologically advanced services to drive customers’ adoption and satisfaction. Recommendations and future studies directions are also discussed.